(untitled) (Comprehensive Journal of Science, 2025)
National identity constitutes the collective conscience of society, and as this conscience matures, societal cohesion increases. When an individual lacks a sense of their identity due to internal or external factors, they develop what we might call an identity crisis, which in turn creates a crisis of awareness that leads to the loss and disintegration of society. National identity is the cornerstone of building cohesive societies. It mobilizes the efforts of individuals to achieve civilizational achievements for society by supporting political, social, and economic stability, confronting external challenges, and stimulating development. National identity can be an important factor in the reconciliation process. By restoring and celebrating shared national values, old divisions can be overcome, consensus can be achieved between different parties, and common interests among citizens, regardless of their orientations, can be restored. Thus, national reconciliation can be successfully achieved and progress can be made toward construction and development.